Office paper recyclability: fibrous characteristics - Benitez, Julieta Beatriz (2014)
Recyclability is the ability of a material to reacquire the same properties it had originally. The aim of this work was to verify the recyclability of three printing and writing papers, from the characteristics of their fibers after two recycles. Three ECF bleached kraft eucalyptus commercial bond papers from Argentina and Brazil were studied (A, B, C). The papers were repulped and refined using different levels and intensities of energy (1st recycle). Laboratory sheets were produced, and they were repulped and refined again (2nd recycle). The microscopic characteristics of repulped papers were obtained by automatic equipment based on image analysis. Differences found in the behavior of the different samples can be explained by fiber parameters. The fiber length was significantly different in the three papers (A > B > C) and globally decreased in the second recycle (about 6%). Sample A had the highest initial fiber length and length/width, but it largely decreased with refining conditions in the 1st recycle (length fall 12%, generating fines by cutting), whereas it fall 9% between the 1st and 2nd recycles, and nothing with refining conditions in the 2nd recycle. Sample B fall by 5% with refining conditions in the 1st recycle, and 9% between the 1st and the 2nd recycle, but suffered few alteration in the second recycle. Fiber length of sample C was unaffected by refining conditions and only decreased 9% between the 1st and 2nd recycles. In all cases, the generated fines increased lightly with refining in the first recycle, but were two-fold higher in the second recycle than in the first one. The fiber coarseness of the 3 samples was similar in the first recycle, but decreases significantly in the 2nd recycle